Podane wyrazenia sprowadz do najprostrzej postaci :
a ) ( a- b )² - ( a - b) ²
b) -⅓ ( 3x -3 )² - 6x
c ) ( 2x + 4xy )² - 4x²
d)( 2a + 3b ) ×( 2a - 3b)
e) x² - y² - ( x+y )× ( x- y )
f) ( 2√3- a ) (2√3 + a )+ ( a√5 +1 ) ( 1- a√5 )


bardzo prosze o rozwiazanie ;)

1

Odpowiedzi

2009-11-12T18:06:47+01:00
A
(a - b)² - (a - b) = 0
b
- 1/3(3x - 3)² - 6x = - 1/3(9x² - 18x + 9) - 6x =
= - 3x² + 6x - 3 - 6x = - 3x² - 3 = - 3(x² + 1)
c
(2x + 4xy)² - 4x² = 4x² + 16x²y + 16x²y² - 4x² = 16x²y + 16x²y² =
= 16x²y(1 + y)
d
(2a + 3b)x(2a - 3b) = x(2a + 3b)(2a - 3b) = x(4a² - 9b²)
e
x² - y² - (x + y)x(x - y) = x² - y² - x(x + y)(x - y) =
= x² - y² - x(x² - y²) = (x² - y²)(1 - x)
f
(2√3 - a)(2√3 + a) + (a√5 + 1)(1 - a√5) = (2√3)² - a² + (a√5)² - 1 =
12 - a² + 5a² - 1 = 11 + 4a